An epigenetic switch in vascular phenotype augments anti-tumor immunity - Dae Joong Kim; Mitchell McGinty; Swetha Anandh; Caroline Riedstra; Yuvraj Sethi; Melanie R. Rutkowski; Andrew C. Dudley (Angiogenesis, 2026)
The abnormal tumor vasculature can present a barrier to the infiltration of anti-tumor immune cells, which impairs immune surveillance and response to immunotherapy. Here, we show that genetically deleting the epigenetic factor DNA methyltransferase 1 ( Dnmt1 ) in endothelial cells (ECs) reduces angiogenesis while imparting profound changes to the tumor immune microenvironment (TIME), including increased proportions of CD4 + memory T cells and NK cells. Depleting CD4 + T cells, or blocking lymphocyte egress from the lymph nodes, rescues tumor growth in mice with conditional deletion of Dnmt1 in ECs ( Dnmt1 iECKO ) and dramatically shortens overall survival, whereas NK cells are dispensable. Tumors implanted in Dnmt1 iECKO mice show reduced vascular branching, elevated expression of VCAM1, increased vessel-associated T cells, and a shift in vascular specification, including increased proportions of immune-permissive post-capillary venules (PCVs) and interferon-stimulated ECs (IFN-ECs). Deleting Dnmt1 in EC cultures strikingly potentiates responses to combinations of IFNγ and TNFα and, notably, up-regulates important T-cell co-stimulatory molecules for memory CD4 + T cells, including Icosl , Cd40 , and Tnfsf4 . Finally, immune checkpoint blockade (ICB) administered to Dnmt1 iECKO mice with experimental melanoma lung metastasis reduces tumor burden, with some mice showing tumor eradication. Our findings identify endothelial Dnmt1 as a key regulator of vascular-mediated anti-tumor immunity, providing a rationale for integrating epigenetic modulation of the vasculature with cancer immunotherapy regimens.